Life lessons from family vacations - Tocquigny, Rick (Taylor Trade Publishing, 2015)
Family vacations: we’ve all taken them. Many view family vacations as some of the greatest learning experiences and transforming moments of life. Life Lessons from Family Vacations is an indulgent adventure unto itself, with many engaging family stories that will remind you of your own travels and perhaps reignite your globetrotting spirit (and courage) to journey with family again